2005
DOI: 10.1165/rcmb.2004-0058oc
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Growth Factor Attenuates Airway Hyperresponsiveness, Inflammation, and Remodeling

Abstract: Hepatocyte growth factor (HGF) is known to influence a number of cell types and their production of regulatory cytokines. We investigated the potential of recombinant HGF to regulate not only the development of allergic airway inflammation and airway hyperresponsiveness (AHR), but also airway remodeling in a murine model. Administration of exogenous HGF after sensitization but during ovalbumin challenge significantly prevented AHR, as well as eosinophil and lymphocyte accumulation in the airways; interleukin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 57 publications
2
69
0
1
Order By: Relevance
“…HGF has been shown previously to be protective in various animal models of immune-mediated diseases such as myocarditis (32,33), glomerulonephritis (30,34), inflammatory bowel disease (35), collagen-induced arthritis (36), pulmonary fibrosis (37), allogeneic heart transplantation (45), graft-vs.-host disease (46), and asthma (47). According to these studies, HGF may ameliorate both Th1-type-dominated (33,36) and Th2-type-dominated (40,47) autoimmune responses.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…HGF has been shown previously to be protective in various animal models of immune-mediated diseases such as myocarditis (32,33), glomerulonephritis (30,34), inflammatory bowel disease (35), collagen-induced arthritis (36), pulmonary fibrosis (37), allogeneic heart transplantation (45), graft-vs.-host disease (46), and asthma (47). According to these studies, HGF may ameliorate both Th1-type-dominated (33,36) and Th2-type-dominated (40,47) autoimmune responses.…”
Section: Discussionmentioning
confidence: 94%
“…According to these studies, HGF may ameliorate both Th1-type-dominated (33,36) and Th2-type-dominated (40,47) autoimmune responses. Interestingly, a recent report demonstrated that, in an experimental model of airway allergy, HGF might repress DC function without up-regulation of IL-10 (40).…”
Section: Discussionmentioning
confidence: 96%
“…HGF, a pleiotropic ligand of the tyrosine kinase receptor c-Met, suppresses both acute and chronic inflammation and injury in a variety of organ systems (12)(13)(14)(15)(16)(17). This protective action was recently ascribed, at least in part, to potent antiinflammatory actions.…”
Section: Discussionmentioning
confidence: 99%
“…Given what is known of the roles of HGF in pathobiology, inactivation by inflammatory peptidases could limit proliferation, migration, or differentiation of c-met-bearing cells in acute response to infection, injury, or allergen exposure. More specifically, selective hydrolysis may oppose HGF effects on epithelial repair in pneumonia, allergic airway inflammation (12), and ischemia-reperfusion injury (13). By interrupting control of epithelial to mesenchymal transformation by HGF, proteolytic inactivation may promote lung and airway fibrosis (11).…”
Section: Discussionmentioning
confidence: 99%